PERAN PENJUAL IKAN DIMASA PANDEMI COVID-19 DALAM MENINGKATKAN KESEJAHTERAAN KELUARGA ( Studi di Pasar Mardika Ambon) - Hobarth Williams Soselisa (BADATI, 2022)
The COVID-19 pandemic requires people to do work from home, this makes people's activities and mobility decline. Even the existence of community activities with the government's policy of implementing community activities (PPKM) which inhibits fish sellers at the Mardika Ambon market with market conditions that look deserted, people's purchasing power has decreased due to not being allowed to carry out activities involving many people, hampered distribution of materials, and a decrease in the number of people involved. fish prices at the level of fishermen and fish sellers. There is a fish seller strategy that is applied during the pandemic, namely fish sellers practice by recording every income earned and then managing it as needed, offering sales results to consumers at low prices during the pandemic, delivering their wares earlier than the time agreed with the previous consumers. , and provide additional fish to consumers who have bought even those who buy fish in large quantities.                    This study aims to determine and analyze how the role of fish sellers during the COVID-19 pandemic in improving family welfare.      The method used in this paper is a qualitative description method. The role of the fish seller is an effort, effort and hard work that is always done. The active role that fish sellers always play is by making offers and adding fish at standard prices to consumers. Meanwhile, the participatory role is the participation of fish sellers to help others, which is shown between sellers, by dividing the place to sell, and making donations for certain or urgent needs. Meanwhile, there is no passive role, because all buyers and sellers are active in the bargaining process and are not just silent. The results of the research at the Ambon Mardika Market show that the life of fish sellers during the COVID-19 pandemic still survives and the income of fish sellers varies. Before the pandemic they had a bigger advantage than when there was a pandemic. However, no loss.